An analysis of the interaction between the prices of crude oil and selected grains and oil seeds in South Africa (2018-2022) - Ledwaba, Kgabo Lucracia (My University, 2024)
The intricate interlinkage of crude oil prices, grains and oilseed prices is an ongoing topic of debate. This study delves into the interaction between crude oil and selected grains and oilseeds prices in South Africa from 2018 to 2022, focusing on maize, soybeans, and wheat. Understanding this relationship is crucial to the agricultural stakeholders given the potential influence of crude oil price fluctuations on the cost of production, transportation, and processing of agricultural products. Employing monthly data, the study adopted a two-pronged approach. First, it evaluated the long and short-term linkages of crude oil, oilseeds and grains prices using Autoregressive Distributed Lag (ADRL) model. Second, it investigated the relationship’s causal direction through Granger causality tests. The results indicated that, based on the ARDL bounds cointegration test, there exists a mixed long run cointegration between crude oil prices and selected grains and oilseed prices. Specifically, there was evidence of long run cointegration between crude oil prices and soybean and maize prices, while no such relationship was found between crude oil and wheat prices. The findings showed that the price of maize increased by 8.199 when crude oil price increased by one unit. Furthermore, although a mixed long run relationship exists, there were no short-run dynamics observed. This implies that crude oil prices do not immediately impact prices of selected grains and oilseeds. Instead, in the short-term, other factors are likely influencing the prices of these commodities in South Africa. These factors could be domestic (production costs, government policies) or global (international prices, trade flows, weather patterns). Given the finding of no direct linkage of crude oil and grain/oilseed prices, policymakers can refocus their efforts on alternative areas to ensure food security and price stability. This could be informed by further studies to generate policy recommendations that include measures to improve domestic production efficiency through subsidies and research, diversification of import sources, and strengthening social safety nets. By challenging the assumed connection between energy and food prices, this study provides policymakers with new insights to ensure new avenues are investigated to properly address food security concerns in South Africa towards the achievement of Sustainable Development Goal (SDG) 2 of reducing hunger.
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2024
Keywords: Petroleum; Crude oil; Oil seeds; Prices; Grain trade -- South Africa; Petroleum products -- Prices -- South Africa; Gasoline -- Prices -- South Africa; Petroleum; Oilseeds -- Analysis